خطاب الضمان في مصرف الراجحي بماليزيا دراسة فقهية تقويمية = Letter of guarantee in Al-Rajhi Bank Malaysia: a juristic evaluative study = Surat jaminan di Bank Al-Rajhi Malaysia: kajian penilaian jurisprudensi - Zakariyah, Habeebullah; Arif, Arif Ali; Ahmad, Shabir Ahmad Molavi (IIUM Press, International Islamic University Malaysia, 2019)
يهدف البحث إلى الوقوف على خدمة خطاب الضمان في مصرف الراجحي بماليزيا والمخارج التي اعتمد عليها المصرف في تقديم هذه الخدمة، ثم تقويم هذه المخارج وبيان مدى انضباطها بالشريعة ثم اقتراح بدائل عما اعتمد عليه المصرف؛ وذلك من خلال بيان معنى خطاب الضمان وأنواعه، وكيفية إجرائه في المصرف والتكييفات الفقهية له مع بيان تكييفه الفقهي في مصرف الراجحي بماليزيا، والمخرج الشرعي الذي اعتمده المصرف على أساسه. وقد اُتِّبع في هذه الدراسة، المنهج الوصفي، والتحليلي، والنقدي. وتوصل البحث إلى أن خطاب الضمان، من أهم الخدمات التجارية يقدمها المصرف لعملائه، والمخرج الشرعي الذي اعتمد عليه المصرف في إصدار خطاب الضمان وأخذ العمولة فيه؛ هو تخريجه على الوكالة بالأجرة إذا كان الخطاب مغطى من قبل العميل تغطية كاملة، فإن أجرته تكون حسب مقدار المبلغ المضمون، أي 1.2% من المبلغ المضمون. وأما إذا لم يكن مغطى أو مغطى جزئيًّا، فهو كفالة عند المصرف، ولا يأخذ المصرف أي أجرة على الكفالة لقاء الضمان، بل يأخذ التكلفة الفعلية، والهيئة الشرعية للمصرف، هي التي تُـحدّد التكلفة الفعلية، وهي غالبًا ثابتة مقدارها أربعمائة رينجيت ماليزي. والمبلغ الذي يأخذه المصرف في خطاب الضمان ثابت سواء أكان المبلغ المضمون قليلاً أو كثيرًا أو وقته طويل أو قصير. فما اعتمده المصرف في إصدار خطاب الضمان وحل إشكالية أخذ الأجرة، يمكن أن يُعتبر خطوة إيجابية وطريقًا صحيحًا للتوصل إلى مقصود صحيح؛ وهو التخلص من الربا وشوائبه، فيعتبر مخرجًا من المخارج الشرعية الصحيحة. الكلمات الأساسية: المخارج الشرعية، خطاب الضمان، مصرف الراجحي، الأجرة. ............................................................................................... This article aims to highlight and explain one of the most important commercial services provided by Al Rajhi Bank Malaysia against prescribed fees – the Letter of Guarantee, identify the Fiqh Adaptation (Takyif Fiqhi) adopted and Shariah Makharij (Devices) that were used by the bank in the design of this product, and evaluate the same in light of Shariah principles, while suggesting more suitable alternative methods that the Bank could adopt. The article follows inductive, analytical and critical approaches to this research. The Shariah Makharij (Devices) relied on by the bank for the purposes of this service depend on whether the Letter is covered by the costumer or not; if the letter is fully covered by the customer, the service is considered by the bank as Wakala bi-al-Ujrah (fee based agency) and the latter charges 1.2% of the guaranteed amount as its fee; and if it is not fully covered or is partially covered, the service is considered a Kafalah (guarantee) by the bank, for which the latter does not charge any fee, except for the actual cost incurred in issuance. The actual cost is determined by the Bank's Shariah Board, which is often fixed at RM400. The amount charged by the bank as fee for the letter of guarantee is fixed, whether the amount guaranteed is small or large or the duration is long or short. The procedure adopted by the Bank in issuing the letter of guarantee and solving the Shariah issue of charging fees on such issuance, is considered a positive step in the right direction and with the correct intent; that is to get rid of usury, and is considered a correct Shariah Makhraj (Device).